Toxicological and nutritional evaluation of plant cell cultures from scurvy grass (Cochlearia danica) and rowan (Sorbus aucuparia) - Felicianna,; Cheung, Ho Lam; Lo, Emily Kwun Kwan; Zhang, Fangfei; Leung, Hoi Kit Matthew; Ismaiah, Marsena Jasiel; Rosa-Sibakov, Natalia; Iannone, Valeria; Gómez-Gallego, Carlos; Kolehmainen, Marjukka; Rischer, Heiko; Nordlund, Emilia; et al. (Frontiers in Toxicology, 2025)
IntroductionPlant cell culture (PCC) technology is currently being developed to produce plant foods partially decoupled from traditional agriculture practices. By now, the safety of the ingredients produced by PCC technology for food or nutritional purposes has to be tested.Materials and methodsIn this study, the oral safety and toxicity of two novel PCCs, scurvy grass (SG) (Cochlearia danica) and rowan (RW) (Sorbus aucuparia), and to characterize the macro- and micronutrient quality, including proteomic profiles, to identify potential allergens.ResultsNutritional composition analysis showed that both SG and RW PCCs profiles are comparable to other berry cell lines with a good amount of protein, dietary fibre and vitamins. Potential allergens were identified via proteomics based on structural similarity. The acute and subacute toxicity profiles of the PCC samples were evaluated based on OECD guidelines. For both PCCs, no deaths, behavioral changes, nor metabolic effects were observed at 2000 mg/kg. In the 28-day repeated oral exposure subacute toxicity study, no mortality or significant adverse clinical, hematological, or metabolic effects were observed for either SG or RW.DiscussionThese findings indicate that the no-observed-adverse-effect level (NOAEL) for both PCCs exceeds 2000 mg/kg. Overall, our findings indicate that the consumption of these PCCs could be considered safe and non-toxic, although further assessments on potential allergens and phytohormone accumulation are necessary to fully ensure consumer safety. This study highlights the oral safety of PCCs for consideration as a novel food ingredient and serve as a basis for evaluating toxicological impacts of PCCs.